P1-S2.52 Risk factors for STIs among MSM attending a sexually transmitted disease clinic in Montreal, Canada. (10th July 2011) - Machouf, N; Thomas, R; O'Brien, R; Vezina, S; Longpré, D; Legault, D; Milne, M; Fafard, J; Trottier, B
Abstract : Background: Often STIs are not diagnosed and not treated because people don't have access to appropriate healthcare screening facilities and to care. At Clinique l'Actuel (Montreal, Canada) we developed Gay Screen Clinic (GSC) as a new concept giving rapid access to men who have sex with men (MSM) to an appointment for STI screening. We then assessed the extend and risk factors of STIs in a population of men having sex with men (MSM) attending the GSC. Methods: We did a retrospective analysis of the last 1000 attendees to the GSC at Clinique l'Actuel in 2009−2010. Multivariable analyses were conducted to identify the factors associated with history of STIs. Results: Participants were all MSM with a mean age of 32 years (ranged from 18 to 70 y). In total, 50% (n=506) of them self reported history of STIs and 236(24%) of them had a positive sexual health screen at this visit. STI diagnoses included genital herpes (n=105, 14 %), condylomes (n=79, 8%), syphilis (n=43, 5%), chlamydia infection (n=32, 3%), HIV (n=10, 1%), Gonorrhoea (n=9, 1%) and HCV (n=5, 1%). 32% of the attendees had sexual relations in bath houses and 43% with anonymous contacts. In multivariate analyses, past history of STI was significantly associated with higher age (OR=1.02, p=0.001), higher number of sexual partners in the last 12  months (OR=1.02, p=0.015), having sexual contact in bath houses (OR=1.46, p=0.021) and with unknown partners met through internet or in backrooms (OR=1.53, p=0.004), using recreational drugs (OR=2.01, p=0.001) and having only male partners (OR=1.60, p=0.023) rather than male and female sexual partners. Conclusions: STIs were common among non HIV MSM attending the GSC in Montreal. Even after many years of prevention campaign MSM still have high risk sexual behaviour. Physician should routinely enquire about drug use of their patients in order to prevent new STIs. Targeting specific sexual networks is needed to be more effective.